A simple method for early age phenotype confirmation using toe tissue from a mouse model of MPS IIIA. (6th March 2014) - Trim, Paul J.; Lau, Adeline A.; Hopwood, John J.; Snel, Marten F.
<x xml:space="preserve">Abstract</x> RATIONALE Determination of genotype can be difficult, especially during the early stages of developing an animal model, e.g. when PCR primers are not yet available. An increase or decrease in specific metabolites can be used as a surrogate marker for genotype; for instance, in homozygous MPS IIIA mice heparan sulphate (HS) is increased. METHODS A simple method was developed for extracting and depolymerising HS from mouse toe tissue using methanolysis under acidic conditions. The sample was lyophilised and resuspended in methanolic HCl. The reaction products are desulphated disaccharides and readily analysable by liquid chromatography/tandem mass spectrometry (LC/MS/MS) in positive ion multiple reaction monitoring mode. Measurements were normalised to a spiked deuterated HS internal standard and to endogenous chondroitin sulphate (CS). RESULTS HS was measured in toe tissue taken from 30 mice in three groups of 10 (normal controls, MPS IIIA homozygotes and heterozygotes). A significant difference was observed between the MPS IIIA homozygotes and the other two groups, making it possible to identify mice with the MPS IIIA genotype based on the measurement of HS. Normalisation to CS was shown to correct for sample variability and reaction efficiency. CONCLUSIONS Analysis of toe tissue provides a simple and rapid way of determining a storage phenotype at 5 to 7 days of age. Significantly, this method does not require any additional samples to be taken from animals, as it utilises tissue that is a by‐product of toe clipping, a method that is routinely used to permanently identify mice. Copyright © 2014 John Wiley & Sons, Ltd.